Smart Practices in Public Administration to End Homelessness: the Example of Scandinavian Countries - Cendrowicz, Dominika (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
Homelessness is a phenomenon for which the scale is growing at an alarming rate in Europe. It leads to the exclusion of people affected by it, to the denying of human dignity, and it constitutes a threat to human health and life. It is a multidimensional phenomenon in its substance and causes that lead to it. Therefore, it is necessary for the European states to take steps to prevent and reduce its scale. This requires thoughtful, sometimes innovative activities that bring with them a serious financial outlay for their implementation. It also concerns Poland, where the basic form of assistance to the homeless people is still a shelter, which is far from the level of assistance provided to the homeless people in the countries of Western Europe, especially in countries such as Finland, Denmark or Norway. The aim of the article is a theoretical overview of the notion of smart practices in public administration to end homelessness in selected Scandinavian countries and its state affair in Poland, using relevant scientific literature. The article provides the reader with information about the homelessness strategies implemented in Finland, Denmark and Norway, and refers them to the Polish conditions.
Keywords: Smart public administration; municipality; non-governmental organizations; smart goals to help reduce homelessness; strategies to prevent homelessness; homeless people